2001
DOI: 10.1200/jco.2001.19.10.2674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Positron Emission Tomography Scanning and Sentinel Node Biopsy in the Detection of Micrometastases of Primary Cutaneous Malignant Melanoma

Abstract: This study demonstrates the limitations of FDG-PET scanning in staging patients with primary melanoma. SNB is the only reliable method for identifying micrometastatic disease in the regional draining node.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 28 publications
6
67
0
7
Order By: Relevance
“…FP findings were most often due to FDG-PET uptake in surgical wounds, inflammatory sites, and benign tumors. [6][7][8][9][10][11][12][13][14][15][16][17][18] Several recent reports have suggested that FDG-PET may be superior to CI for the identification of metastases; some have suggested that FDG-PET may be able to replace CI as a screening modality for these patients. 13,14,20 In a prospective study of 100 patients with AJCC stage I to III melanoma, Rinne et al 13 directly compared the sensitivity and specificity FDG-PET with those of CI.…”
Section: Discussionmentioning
confidence: 99%
“…FP findings were most often due to FDG-PET uptake in surgical wounds, inflammatory sites, and benign tumors. [6][7][8][9][10][11][12][13][14][15][16][17][18] Several recent reports have suggested that FDG-PET may be superior to CI for the identification of metastases; some have suggested that FDG-PET may be able to replace CI as a screening modality for these patients. 13,14,20 In a prospective study of 100 patients with AJCC stage I to III melanoma, Rinne et al 13 directly compared the sensitivity and specificity FDG-PET with those of CI.…”
Section: Discussionmentioning
confidence: 99%
“…A few radiologists are in favor of staging regional lymph node basins in stage I-II melanoma with high-resolution ultrasonography [24][25][26]. However, the general opinion is that targeted high-resolution ultrasonography is not an effective substitute for SLNB in patients with primary melanoma [27][28][29][30]. Several authors investigated the use of chest x-rays in staging and concluded that its use is questionable, because of low detection rates, high false-positive percentages and subsequent high patient anxiety [31][32][33].…”
Section: Reviewmentioning
confidence: 99%
“…This raises the question of the importance of this relatively new technique in staging any melanoma patient. In several studies, FDG-PET has shown limited sensitivity to detect microscopic lymph node metastases in this selected group of patients with stage I and II melanoma [27][28][29][92][93][94]. Mijnhout et al documented in a systematic review and meta-ana lysis of the literature from the 1990s, a pooled sensitivity of 79% and a specificity of 86% for the detection of melanoma metastases (both lymph nodes and distant) [93].…”
Section: Pet In Melanoma Stagingmentioning
confidence: 99%
“…In a prospective study of 50 patients with primary melanomas (thickness > 1 mm or lymphatic invasion), Acland et al [29] compared the sensitivity of 18 F-FDG PET with SLNB for the detection of micrometastatic malignant melanoma. All of the patients underwent 18 F-FDG PET and subsequent SLNB.…”
Section: Comparison Of 18 F-fdg Pet (Pet/ct) and Slnb For Detecting Rmentioning
confidence: 99%